Deconstructing Development Discourse: Buzzwords and Fuzzwords - Cornwall, Andrea; Eade, Deborah (Oxfam & Practical Action Publishing, 2010)
Writing from diverse locations, contributors critically examine some o f the key terms in current development discourse. Why should language matter to those who are doing development? Surely, there are more urge nt things to do than sit around mulling over semantics?